Health care expenditure and the state of health care sector in selected European Union countries - Joanna Hady; Małgorzata Leśniowska (e-Finanse: Financial Internet Quarterly, 2011)
The article deals with the issue of health care, focusing on expenditure allocated to it. The first part of the article reviews some selected European Union countries, analyzing their expenditure on their health care sectors. The second part brings an analysis of expenditure on health care in Poland. Basing on this analysis we determine the state of the Polish health care sector. Moreover, as regards the Polish health care sector, we indicate the expenditure forecasts. The article concludes with a comparison of the state of the Polish system to the state of the systems in other European countries.
Keywords: I11; I15; I18; 330; expenditure; health care; European Union